Have Fintech companies higher values than their traditional financial peers? - Vila, Yoandy Santana (2021)
The main objective of this paper is to prove that fintech companies have more value than traditional financial companies. To achieve that, we selected a sample of 13 fintech firms from the KBW Nasdaq Financial Technology Index plus 93 firms from the NASDAQ Financial-100 Index, all of them listed on the NASDAQ Composite Index. We created three portfolios: fintech firms (13); traditional financial firms (93) and the full market portfolio (106). Using the three-factor model of Fama and French, we compared the weekly returns of the fintech portfolio with the two others as benchmarks. Our empirical results showed statistically significant evidence that the fintech portfolio outperform both benchmarks portfolios, and so we can prove our hypothesis that the fintech companies create more value than traditional financial companies.